Early versus late repair of diaphragmatic palsy after congenital heart surgery: A comparative study - Morsy, Ahmed Adel; Zalat, M.; Elatafy, Elatafy E. (International journal of health sciences, 2021)
Background: Diaphragmatic palsy (DP) following pediatric cardiac surgery is a known complication because of phrenic nerve injury, which can significantly impact respiratory function and overall recovery. The aim is to evaluate the effect of early diaphragm plication on clinical outcomes in pediatric patients who have undergone cardiac surgery and to compare it with late diaphragm plication. Methods: This retrospective study carried out on 46 cases with DP; 26 underwent early diaphragmatic plication, while 20 patients subjected to late Plication. Diagnosis of DP was primarily based on clinical signs, confirmed with bedside ultrasonography and fluoroscope. The early plication being defined as surgery performed in 7 days of DP diagnosis and late plication as surgery performed after 7 days. All plications were done through standard thoracotomy using non absorbable sutures to flatten the diaphragm. Results: Patients who underwent early diaphragmatic plication were significantly younger (P value = 0.02), and had fewer complications including the need for noninvasive ventilation (P value = 0.031), ventilator acquired pneumonia (P value = 0.011), and recurrent lung collapse (P value = 0.040).